2016
DOI: 10.1016/j.molp.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Light Intensity and Floral Transition: Chloroplast Says “Time to Flower!”

Abstract: Flowering represents a pivotal developmental transition from the vegetative stage to the reproductive stage. The timing of flowering must be carefully controlled under ever-changing environmental conditions to ensure successful reproduction. Extensive genetic and molecular biological analyses in the model species Arabidopsis thaliana have identified important regulators of flowering time and revealed a complex network of highly interconnected pathways that are regulated by seasonal cues (e.g., light and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The sessile plants are directly exposed to the seasonally changed light, which also results in the change of photoperiod and temperature. Accumulated data have confirmed that flowering was triggered by the light alterations . In both annual herbal plants and perennial woody plants, light plays a central role in flowering regulation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The sessile plants are directly exposed to the seasonally changed light, which also results in the change of photoperiod and temperature. Accumulated data have confirmed that flowering was triggered by the light alterations . In both annual herbal plants and perennial woody plants, light plays a central role in flowering regulation.…”
Section: Introductionmentioning
confidence: 87%
“…Accumulated data have confirmed that flowering was triggered by the light alterations. [18][19][20][21][22] In both annual herbal plants and perennial woody plants, light plays a central role in flowering regulation. The well-known mechanism is that light period is measured by the circadian clock in leaves, which controls the release of florigen to the shoot apex for subsequent floral initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has showed that the expression of ATH1 could activate FLC , a flowering repressor [ 16 , 33 , 34 , 35 ]. However, it is not known if OFP1 function in regulation of FLC expression involves an interaction between OFP1 and ATH1.…”
Section: Resultsmentioning
confidence: 99%
“…Chloroplasts are the site of photosynthesis and multiple anabolic reactions essential for growth, development, and reproduction [41]. Signals from chloroplasts can modulate nuclear gene expression and regulate plant development, including flower development [4244]. An Arabidopsis mutant, lacking the chloroplast-localized rhomboid protease, exhibited either a double stigma or a single stigma with distortions in shape and size [45].…”
Section: Discussionmentioning
confidence: 99%